A Comparison between Ratio and Gradient Technique in Discriminating Cirrus Clouds from Tropospheric Aerosols over Water in MODIS Data - Asmala, A.; Abd Rahman, Mat Amin; Fadhli , Ahmad; Mustafa, Mamat; Khiruddin, Abdullah (HIKARI LTD, 2014)
This study aims to compare between ratio technique (RT) and gradient technique (GT) to distinguish cirrus cloud from tropospheric aerosol over water in MODIS data. Both techniques make use of 1.375 µm and 1.240 µm band and are applied to five different scenes. The outcomes from both techniques are compared using an error matrix in which revealing that the GT has a very high agreement with RT in distinguishing cirrus cloud from tropospheric aerosol in MODIS data.